Developing countries and MNEs: extending and enriching the research agenda - Ramamurti, Ravi (Journal of International Business Studies, 2004)
Foreign direct investment (FDI) through multinational enterprises (MNEs) has emerged in the last decade as the principal source of foreign capital for developing countries. Meyer (this issue) underlines the need for international business (IB) scholars to understand the impact of these investments on host developing countries. He offers a useful assessment of the literature and proposes a rich set of questions for further research. However, his research agenda can be extended and enriched in two ways. First, IB scholars must study, as they always have, causation in the opposite direction—namely, the impact of developing country context on MNE behavior and the co–evolution of these two variables over time. In doing so, they must incorporate into their models contemporary issues, such as the continued inadequacy of rules for FDI in infrastructure sectors, or the clever means by which MNEs are rewriting the global rules under which they operate in developing countries (e.g., on intellectual property rights). Second, IB scholars must pay more attention to topics that are not mainstream within the field but are of great importance to developing countries. Examples include the behavior and performance of a new generation of home-grown MNEs, the role of diaspora in homeland FDI (in countries like China and India), and the implications of global outsourcing of services.